PENGARUH PENGISIAN LEMBAR JAWABAN PEMERIKSAAN RADIOLOGI TERHADAP KUALITAS KODIFIKASI PENYAKIT TUBERCULOSIS OF LUNG WITHOUT MENTION OF BACTERIOLOGICAL OR HISTOLOGICAL CONFIRMATION (A16.2) DI RUMAH SAKIT PKU MUHAMADIYAH PETANAHAN - Rachmadi, Triyo; Ali Mahmud, Haidar (Jurnal Infokes, 2021)
The answer sheet of radiology examination as a supporting sheet to assist the doctor in establishing the diagnosis of disease and the accuracy of the diagnosis greatly affects the code of the disease itself.Codification of Tuberculosis of lung codification without mention of bacteriological or histological confirmation depends on the cmpletenessof the answer sheet radiological examination in the patient’s medical records. The purpose of this research is to know the effect of filling the answer sheet of radiology examination to the quality of the Tuberculosis of lung codification without mention of bacteriological or histological confirmation in the hospital PKU Muhamadiyah petanahan. This research uses qualitative descriptive method with sample of 30 medical record files and 3 respondents namely Director of Hospital, Head of Medical Record and Officer of Coding. Data collection techniques used are observation, interview and literature study. Indicators on the answer sheet of radiology examination are 11 Patient identification, date and time, result of anamnesa, result of physical examination, diagnosis, management plan, treatment of action, other service, approval of action, clinical observation note and treatment result, name and signature of doctor while indicators for the quality of disease codification are 4, namely diagnostic accuracy, diagnostic clarity, using ICD-X and codification accuracy.The result of observation of answer sheet of radiology examination, complete indicator there are 4 whereas incomplete there is 7. The result of observation of quality of disease codification that fulfill indicator there are 4 while that does not fulfill indicator that is not exist. Results of interviews on 3 respondents good results. From the results of this study there is an influence between the filling sheet answer radiology examination of tuberculosis of tuberculosis of disease quality without mention of bacteriological or histological confirmation. As for suggestion than is make standard opertional precedureand socialization to radiologi officer.